2023
DOI: 10.1097/mao.0000000000003934
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying Risk of Future Growth Among Sporadic Vestibular Schwannomas

Abstract: Objective In certain cases, clinicians may consider continued observation of a vestibular schwannoma after initial growth is detected. The aim of the current work was to determine if patients with growing sporadic vestibular schwannomas could be stratified by the likelihood of subsequent growth based on initial growth behavior. Study Design Slice-by-slice volumetric tumor measurements from 3,505 serial magnetic resonance imaging studies were analyzed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…By contrast, a 2016 systematic review that compiled data from many studies of VS growth behavior found that 50.1% of followed tumors demonstrated growth at 5 years (4). Numerous studies have identified a lower rate of growth for small tumors compared with larger tumors (5). This implies that reviews encompassing all tumor sizes may overestimate the growth for small tumors.…”
mentioning
confidence: 99%
“…By contrast, a 2016 systematic review that compiled data from many studies of VS growth behavior found that 50.1% of followed tumors demonstrated growth at 5 years (4). Numerous studies have identified a lower rate of growth for small tumors compared with larger tumors (5). This implies that reviews encompassing all tumor sizes may overestimate the growth for small tumors.…”
mentioning
confidence: 99%